Development strategy for marine ecotourism area in Pohuwato District (a case study at Pohon Cinta Beach and Tanjung Maleo Beach) - Veggy Arman; Abdul Hafidz Olii; Hasim Hasim (Gorontalo State University, 2021)
This research aims to know the marine ecotourism suitability, carry capacity of the area, and to formulate a strategy for managing ecotourism areas in Pohuwato District. This research is conducted at the Pohon Cinta beach and Tanjung Maleo beach. The data analysis is done by measuring the land suitability index, area carrying capacity, and SWOT Analysis. The result of the suitability analysis of beach tourism shows that the Pohon Cinta beach tourism area is suitable for beach recreational activities, boating, banana boating, and jet skiing as well as is suitable for swimming. Tanjung Maleo beach area is suitable for all activities, such as beach recreational activities, swimming, boating, banana boating, and jet skiing. Pohon Cinta beach tourism area can accommodate around 9.840 people/day, and Tanjung Maleo can accommodate around 2.640 people/day. Strategy for managing the tourism area of Pohuwato District, including promoting tourist attraction, formulating policies, determining coastal areas that need protection, coordinating each related party, inviting the community and visitor to take part in preserving the environment, improving the quality of torism area, improving coordination between the district government and the community, socialization of coaching and educational campaigns, increasing natural disaster mitigation efforts, the government monitoring, adding tourist facilities, and developing non-govermental activities.